Studi Literatur Platform Digital Sebagai Sarana Dalam Mengembangkan UMKM - Oktalia Juwita; Arizona Firdonsyah; Mahrus Ali; Aris Puji Widodo; R. Rizal Isnanto (INFORMAL: Informatics Journal, 2022)
Today's increasingly rapid use of digital technology has created many new opportunities for organizations in all industrial fields. Digital transformation has a positive impact on innovation and company performance based on the theory of the resource-based view. The growth of Small and Medium Enterprises (SMEs) and their relatively high role in the community's economy, is also accompanied by several problems that arise in the face of the current digitalization era. The main challenges in the digitization process for SMEs are limited financial resources, limited knowledge resources, and limited technology awareness. An ecosystem-based digital platform enables SMEs to integrate strategic knowledge sources while configuring internal and external resources to better respond to a dynamic and volatile environment.